Azinäre Pankreasneoplasien: vergleichende molekulare Charakterisierung = Pancreatic acinar neoplasms : comparative molecular characterization - Bergmann, Frank (Der Pathologe, 2016)
Pancreatic acinar cell carcinomas are biologically aggressive neoplasms for which treatment options are very limited. The molecular mechanisms of tumor initiation and progression are largely not understood and precursor lesions have not yet been identified. In this study, pancreatic acinar cell carcinomas were cytogenetically characterized as well as by molecular and immunohistochemical analyses. Corresponding investigations were carried out on pancreatic ductal adenocarcinomas and pancreatic neuroendocrine neoplasms augmented by functional analyses. We show that pancreatic acinar cell carcinomas display a microsatellite stable, chromosomal unstable genotype, characterized by recurrent chromosomal imbalances that clearly discriminate them from pancreatic ductal adenocarcinomas and neuroendocrine neoplasms. Based on findings obtained from comparative genomic hybridization, candidate genes could be identified, such as deleted in colorectal cancer (DCC) and c-MYC. Furthermore, several therapeutic targets were identified in acinar cell carcinomas and other pancreatic neoplasms, including epidermal growth factor receptor (EGFR), L1 cell adhesion molecule (L1CAM) and heat shock protein 90 (HSP90). Moreover, L1CAM was shown to play a significant role in the tumorigenesis of pancreatic ductal adenocarcinoma. Functional analyses in cell lines derived from pancreatic neuroendocrine neoplasms revealed promising anti-tumorigenic effects using EGFR and HSP90 inhibitors affecting the cell cycle and in the case of HSP90, regulating several other oncogenes. Finally, based on mutational analyses of mitochondrial DNA, molecular evidence is provided that acinar cell cystadenomas (or better cystic acinar transformation) represent non-clonal lesions, suggesting an inflammatory reactive non-neoplastic nature.
Gesehen am 24.08.2017